Prediction of sport adherence through the influence of autonomy-supportive coaching among Spanish adolescent athletes - Almagro, B. J.; Saenz-Lopez, P.; Moreno, J. A. (Journal of Sports Science & Medicine, 2010)
The purpose of this study was to test a motivational model of the coach-athlete relationship, based on self-determination theory and on the hierarchical model of intrinsic and extrinsic motivation. The sample comprised of 608 athletes (ages of 12-17 years) completed the following measures: interest in athlete's input, praise for autonomous behavior, perceived autonomy, intrinsic motivation, and the intention to be physically active. Structural equation modeling results demonstrated that interest in athletes' input and praise for autonomous behavior predicted perceived autonomy, and perceived autonomy positively predicted intrinsic motivation. Finally, intrinsic motivation predicted the intention to be physically active in the future. The results are discussed in relation to the importance of the climate of autonomy support created by the coach on intrinsic motivation and adherence to sport by adolescent athletes. Further, the results provide information related to the possible objectives of future interventions for the education of coaches, with the goal of providing them with tools and strategies to favor the development of intrinsic motivation among their athletes. In conclusion, the climate of autonomy support created by the coach can predict the autonomy perceived by the athletes which predicts the intrinsic motivation experienced by the athletes, and therefore, their adherence to athletic practice.